Kontribusi Filsafat Islam Terhadap Pendidikan Islam; (Studi Analisis al-Ghazālī dan Ibnu Rusyd) - Daru Nur Dianna (Universitas Darussalam Gontor, 2020)
This article aims to take a lesson and inspiration from of two Muslim thinkers al-Ghazālī and Ibn Rushd in their intellectual legacy in Islamic philosophy. The legacy of these two figures has an influence on the current development of Islamic thought and Islamic education until now. Its influence is not only in the Islamic world, but also in the Western world. One of the interesting issues in examining the thoughts between these two figures is the contradiction between philosophical aspect in the al-Ghazālī’s work in Tahāfut al-Falāsifah and Rushd’s work in Tahāfut at-Tahāfut. The value of this article is to take inspiration from the discussion, then use it to develop Islamic education in Modern Era. This study uses a library research methodology of the work of the two figures and from a journal or research that analyzes the discussion of the two figures. The results of this study are: providing insight into how to benefit from a culture of literacy and scientific dialogue; open and productive attitude, the importance of critical and systematic thinking; and provides insights into the Islamic worldview of Muslim scientists in the era of modern science to understand the concepts of knowledge and causality.